ALPHA ADDUCIN GENE POLYMORPHISM IS MORE COMMON IN MALE AS COMPARE TO FEMALE IN ESSENTIAL HYPERTENSIVE PATIENTS. (June 2022) - Naz, Qulsoom; Verma, Narsingh; Serajuddin, M.; Patel, M.L.
Abstract : Objective: Essential hypertension is a complex and multifactorial disorder resulting from environmental and genetic factors, and their interactions. Alpha nalysed-1 (ADD1) gene is salt sensitive gene which has its role in etiology of essential hypertension via renal sodium reabsorption. Therefore, the G460T polymorphism of ADD1 gene may be associated with new onset of CVD & stroke under the influence of essential hypertension. Aim: To assess the relationship between male & female genetic polymorphism (ADD1 G460T polymorphism) under influence of essential hypertension. Design and method: Materials and Methods: We recruited total 255 study subjects, 110 normotensive as control (63 male and 47 females), 145 hypertensive patients (85 male and 60 females) and 240 hypertensive. All study samples were genotyped for ADD1 polymorphic alleles and nalysed the relationship between different genotypes with respect to anthropometric and clinical parameters. Results: Results-Clinical and anthropometric parameters (such as SBP, DBP, FBG, height, weight, HbA1c, BMI & urinary electrolyte) of study population were found highly statistically significant (p < 0.05) at base value. Further, genotype wise comparison of all the above parameters revealed most of them as non-significant (p> 0.05). Whereas, comparison between genotype frequencies in essential hypertensive patients, specifically in female (p = 0.027) and male (p = 0.015) and in combination with both female (p = 0.017) and male (p = 0.005) revealed a higher HbA1c level in variant T allele. In case of essential hypertensive patients, male population showed a highly statistically significant (p = 0.003) difference in GT & TT allele frequency in aplpha adducing gene polymorphism. Conclusions: Anthropometric & Clinical parameters may be the indicative factors for essential hypertension. Variant T allele of ADD1 gene may be considered as the risk factor for the development of stroke & cardiovascular diseases in essential hypertensive patients.